THE INFLUENCE OF LEARNING INTEREST AND SELF-EFFICACY OF JUNIOR HIGH SCHOOL STUDENTS ON CRITICAL THINKING ABILITY IN SOLVING MATHEMATICAL PROBLEMS - Trisna Elimni Delesep Benu; Ismail Ismail; A’yunin Sofro (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to find out whether there is an influence of learning interest and self-efficacy of junior high school students on critical thinking skills. This study uses a type of quantitative research, which was conducted at SMPN 48 Surabaya on SPLDV material. The research subjects were 32 students in grade VIII B. This research instrument consisted of a learning interest questionnaire, a self-efficacy questionnaire, and a critical thinking ability test. The data analysis technique uses two stages, namely assumption test and hypothesis test. The assumption test is in the form of normality test, multicollinearity test and heteroscedasticity test. After conducting the assumption test, modeling of the regsession was carried out and continued with a simultaneous test, namely the F test. The data analysis in this study used the help of SPSS version 30.0. The results of the study showed that there was a significant influence of the learning interest and self efficacy of junior high school students on the ability to think critically as shown by the significance value of < 0,0001 > 0,005.